In-service training needs of the faculty of Febias College of Bible - De Felipe, Aurea Vicente Bentillo 1948-
The author aimed to determine the in-service training needs of the faculty of FEBIAS College of Bible during School Year 1985-1986. She made use of the normative-descriptive method. A questionnaire was used as the research tool.